2018
DOI: 10.1111/jdv.14739
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and odds of depression in patients with vitiligo: a meta‐analysis

Abstract: This meta-analysis review indicates that the prevalence of depression is high in patients with vitiligo. The HDRS questionnaire may be the most sensitive tool for testing the depressive symptoms among patients with vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 35 publications
2
44
3
4
Order By: Relevance
“…Our results were consistent with the results of previous studies, which suggest women with vitiligo had poorer quality of life [33,36,37,42]. However, other studies concluded that vitiligo patients suffer more from depression and anxiety [20,[38][39][40][41]. On the contrary to other studies, this study showed that the women were more anxious and hopeless.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were consistent with the results of previous studies, which suggest women with vitiligo had poorer quality of life [33,36,37,42]. However, other studies concluded that vitiligo patients suffer more from depression and anxiety [20,[38][39][40][41]. On the contrary to other studies, this study showed that the women were more anxious and hopeless.…”
Section: Discussionsupporting
confidence: 91%
“…Studies showed poorer quality of life in women with vitiligo compared to men with vitiligo [36], in married women in comparison with single women [33], and in Muslim women in comparison with Muslim men [37]. Nonetheless, depression [20,25,38,39], anxiety and hopelessness [40,41], were more reported in vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the earlier meta-analysis, the prevalence of depression in women with vitiligo was significantly higher than that in men. 12 However, we found no statistically significant differences in depression between genders, age groups, skin phototypes, types of vitiligo and involved areas.…”
Section: Depressioncontrasting
confidence: 68%
“… 9 – 11 A meta-analysis conducted by Wang et al, found that vitiligo patients were 4.96 times more likely to have depressive symptoms compared to controls. 12 Psychodermatology is a relatively new area of patient care that focuses on the interaction between the skin and the mind. Thus, in addition to treating the clinical symptoms of vitiligo, dermatologists can also play an important role in helping patients to psychologically adjust to, and accept, their condition.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 meta-analysis of the prevalence and odds of depression in patients with vitiligo found a wide range of prevalence between 8% and 33% across 17 studies, depending on the diagnostic tool used. [10]. Meanwhile, anxiety in patients with vitiligo warrants higher awareness and greater attention as it can negatively affect adherence to treatment and overall quality of life [11].…”
Section: Introductionmentioning
confidence: 99%